Yaqqim-Addu of Sagaratum: The Correspondence of a District Governor in the Kingdom of Mari - Coleson, Joseph Edward (1982)
Ph.D. Dissertation; Order No. DA8220096, cf. DissAbstr 43/08 (February 1983) 2755-A; abstract not available.